Thermal and microstructural investigation of Cu-Al-Mn-Mg shape memory alloys - Canbay, Canan Aksu; Ozgen, Soner; Genc, Zuhal Karagoz (Springer Heidelberg, 2014)
There are many studies to improve the properties of Cu-Al-Mn shape memory alloys, such as high transformation temperatures, ductility and workability. Most of them have been performed by adding a quaternary component to the alloy. In this study, the effect of trace Mg addition on transformation temperatures and microstructures of three different quaternary Cu-Al-Mn-Mg alloys has been investigated using thermal analysis, optical microscopy and XRD techniques. The transformation temperatures are within the range of 120-180 degrees C, and they have not changed significantly on decreasing the Mn content, replacing with Mg. The fine precipitates have been observed in the alloys with the Mg content up to 1.64 at%. Calculated entropy change and XRD analysis reveal that the alloys with high Al content have mainly 18R-type structure which could be responsible for good ductility and workability.
Keywords: Martensitic-Transformation; Grain-Size; Phase; Stability; Decomposition; Fabrication; Behavior